The problem of gender identity in the novel “Easy Breathing” by I. Bunin - Smirnov, Ivan (Slavia Centralis, 2022)
In the article, the author questions the normative sexuality of the heroes of I. Bunin’s short story "Easy Breathing", and shows their indefinite psychogender identity through the prism of V. Rozanov’s teachings about the people of the "moonlight". The psychophysiological characteristics and negative experience of gender-role behaviour provoke a mixture of binary oppositions and a powerful spiritual collapse of individuals, which, in one case, leads to the death of a young girl, and in the other, to the mental suffering of an adult woman. Sexual attraction, personified in a lesbian dyad in love and passion, leads to a personal crisis, which entails contradictions in psychological, social and moral aspects.
Keywords: people of the moonlight; non-binary gender; homosexuality; sexual psyche; lunar anomaly